PERAN KEPALA SEKOLAH DALAM MEMBENTUK KARAKTER DISIPLIN SISWA DI SMK SWASTA KARYA BUNDA MEDAN - Nazri, Al-Hafiz; Mesiono, Mesiono; Marpaung, Syafri Fadillah (Universitas Islam Negeri Sumatera Utara Medan, 2021)
The study of the role of school principals begins with the standards of principals as stated in Permendiknas No. 13 of 2007. There are two aspects, qualifications and competencies as initial capital as school principals. The capital owned by the principal needs to be encouraged with five roles as an effective leader. The five roles are as exciting catalyst, visionary motivator, controlled liaison, determined implementer and wise expert. A leader must be disciplined, the factors that influence discipline include: the existence of goals and abilities, exemplary, justice, supervision, punishment, assertiveness, and human relations.Leadership, Principal, Discipline Character.